Influence of temperature and soil moisture on some population growth parameters of Cyrtomenus bergi (Hemiptera: Cydnidae) - Riis, L; Esbjerg, P; Bellotti, Anthony C. (Florida Entomological Society, 2005)
Abundance of Cyrtomenus bergi Froeschner has been reported regularly under moist and damp conditions. The influence of temperature and soil moisture on development time and mortality of first, third, and fifth instars, longevity and fecundity of C. bergi adult females, as well as hatching time and rate of eggs were determined under laboratory conditions at different temperature and soil moisture levels. Population growth is optimal around 26°C (constant temperature) and a soil moisture regime ranging from moist (field capacity) to wet soil (between field capacity and water saturation). Wet soil (44% gravimetric soil water) promotes high mean fecundity in young adult females, reducing generation time and favoring population growth compared to that seen in moist soil (33.5% gravimetric soil water, field capacity). The lower temperature threshold for development was 14.7°C. Neither egg hatching nor molting from fifth instars to adults occurred above 31°C. The lower soil moisture threshold for immature development was between dusty (19% gravimetric soil water) and very dry soil (22% gravimetric soil water) and between very dry and dry (25.5% gravimetric soil water, wilting point) for adult female survival and oviposition. Third instars were most tolerant to extreme temperatures. These abiotic limitations to population growth together with other findings concerning host plant regime and movement in soil may explain patterns of local and regional abundance.